Patients' experiences and satisfaction with health care: results of a questionnaire study of specific aspects of care. Issue 4 (1st December 2002) - Jenkinson, C; Coulter, A; Bruster, S; Richards, N; Chandola, T
Abstract : Objective: To determine what aspects of healthcare provision are most likely to influence satisfaction with care and willingness to recommend hospital services to others and, secondly, to explore the extent to which satisfaction is a meaningful indicator of patient experience of healthcare services. Design: Postal survey of a sample of patients who underwent a period of inpatient care. Patients were asked to evaluate their overall experience of this episode of care and to complete the Picker Inpatient Survey questionnaire on specific aspects of their care. Sample: Patients aged 18 and over presenting at five hospitals within one NHS trust in Scotland. Method: 3592 questionnaires were mailed to patients' homes within 1 month of discharge from hospital during a 12 month period. Two reminders were sent to non-responders; 2249 (65%) questionnaires were returned. Results: Almost 90% of respondents indicated that they were satisfied with their period of inpatient care. Age and overall self-assessed health were only weakly associated with satisfaction. A multiple linear regression indicated that the major determinants of patient satisfaction were physical comfort, emotional support, and respect for patient preferences. However, many patients who reported their satisfaction with the care they received also indicated problems with their inpatient care as measured on the Picker Inpatient Survey; 55% of respondents who rated their inpatient episode as "excellent" indicated problems on 10% of the issues measured on the Picker questionnaire. Discussion: The evidence suggests that patient satisfaction scores present a limited and optimistic picture. Detailed questions about specific aspects of patients' experiences are likely to be more useful for monitoring the performance of various hospital departments and wards and could point to ways in which delivery of health care could be improved.